Corn distiller’s dried grains with solubles as a target for fermentation to improve bioactive functionality for animal feed and as a source for a novel microorganism with antibacterial activity - Christopher, Ashish; Ostrander, Jesse; Mathew, Jithin; Sarkar, Dipayan; Shetty, Kalidas (Frontiers in Food Science and Technology, 2023)
Plant-based bioenergy by-products such as corn distillers’ dried grains with solubles (DDGS) are widely utilized as animal feed sources and feed ingredients due to their balanced nutritional profile and animal health protective functional qualities. Bioprocessing of this bioenergy by-product using beneficial lactic acid bacteria (LAB)-based fermentation strategy to improve animal-health targeted functional qualities has wider relevance for animal feed applications. In this study, liquid extracts of corn DDGS were fermented with Lactiplantibacillus plantarum and Lactobacillus helveticus. The unfermented and fermented extracts were then analyzed (at 0, 24, 48 and 72-h) for their total soluble phenolic content (TSP), phenolic profile, antioxidant activity via ABTS and DPPH radical scavenging activity, and antimicrobial activity against the gut pathogen Helicobacter pylori using in vitro assay models. Statistical differences in antioxidant activity and phenolic content were observed among the unfermented and fermented extracts. The major phenolic compounds detected in corn DDGS were gallic, dihydroxybenzoic, p-coumaric, caffeic and ferulic acid, and catechin. Antimicrobial activity against H. pylori was observed for the unfermented extracts and the antimicrobial activity was attributed to the growth of a corn DDGS-endemic culture. The culture was isolated, sequenced, and identified as Bacillus amyloliquefaciens. Results of this study indicated that processing strategies of by-products such as LAB- based fermentation of corn DDGS could affect its bioactive-linked functional qualities due to microbial interaction with the phytochemicals. Furthermore, plant by-products can serve as novel sources of beneficial microflora that have relevance in wider agriculture, food safety, and therapeutic applications.